Hashimoto's encephalopathy with cerebellar ataxia as the main symptom: A case report and literature review - Wei, Chunxiao; Shen, Yanxin; Zhai, Weijie; Shang, Tianling; Wang, Zicheng; Wang, Yongchun; Li, Mingxi; Zhao, Yang; Sun, Li (Frontiers in Neurology, 2022)
Hashimoto’s encephalopathy (HE), is also known as steroid responsive encephalopathy associated with autoimmune thyroiditis (SREAT), has a variety of clinical manifestations, with various neuropsychiatric characteristics, including tremor, transient aphasia, seizures, altered consciousness, myoclonus, cognitive impairment and psychiatric manifestations. The hallmark presenting feature is a nonspecific encephalopathy characterized by alteration of mental status and consciousness ranging from confusion to coma and impaired cognitive function, while those with cerebellar ataxia as the main manifestation is rare and only 20 cases have been reported. We reported a case of Hashimoto's encephalopathy with cerebellar ataxia as the main manifestation, elevated anti-thyroid antibodies (anti-TPO/TG) and normal thyroid function. The symptoms of cerebellar ataxia improved after cortisol hormone treatment. Meanwhile, we reviewed the clinical features of those 20 cases of HE with cerebellar ataxia as the core symptoms. In conclusion, based on our case findings and literature review, the diagnosis of HE should be suspected in case of encephalopathy without obvious cause, to quickly start effective treatment.